Prevalence of benign bone lesions of the lower extremity in the pediatric spinal disorders: a whole-body imaging study. Issue 6 (31st January 2022) - Yucekul, Altug; Karaytug, Kayahan; Bakircioglu, Sancar; Zulemyan, Tais; Sirin, Basak Kumbasar; Karaarslan, Ercan; Yilgor, Caglar; Alanay, Ahmet
Abstract : There is a paucity of knowledge about benign bone lesions. The advances in imaging methods can screen bone lesions incidentally, and missing information can be provided. The aim of the study is to collect information about the prevalence and natural history of benign bone lesions with the use of whole-body biplanar slot-scanning imaging (EOS). EOS images acquired between 2015 and 2020 were retrospectively analyzed. Anatomical locations of lesions, number of lesions with polyostotic involvement and radiographic features of each were recorded. Fibrous lesions were further categorized according to the transition stages. The natural course was noted as remained in the same stage, progressed and disappeared during follow-up. A total of 1944 EOS images of 1378 (936 women and 442 men) patients were analyzed. The mean age was 12.3 (5–18) years. Bone lesions of the lower extremities were found in 278 scans (14.3%) of 196 (139 women and 57 men) patients (14.2%). Monostotic lesions were observed in 172 patients, and 24 had polyostotic lesions. The prevalence of lesions was 10.5%, 1.8%, 1.7%, 1.7% and 1.4‰ for fibrous cortical defect (FCD), nonossifying fibroma (NOF), osteochondroma, bone island and simple bone cyst, respectively. Among 145 FCDs, 55.2% of the lesions were stage A, 27.6% were stage B, 9.6% were stage C and 7.5% were stage D. EOS images acquired predominantly for spinal pathologies revealed a prevalence of 14% of benign bone tumors in the lower extremities. With the developments in imaging methods, the probability of encountering incidental lesion increases, and information about bone pathologies can be gathered.